Karakteristik Organoleptik, Kapasitas Antioksidan dan Kadar Serat Pada Kue Lumpur Dengan Penambahan Pure Kulit Buah Naga Merah (Hylocereus polyrhizus) - Cahyani, Ni Putu Diva Ardyan Mas; Antarini, Anak Agung Nanak; Tamam, Badrut (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Mud cake characterized by yellow color, round shape and soft texture like mud. This research to determine the effect of red dragon fruit peel pure addition on the characteristics of mud cake. This research is an experimental method using Randomized Group Design (RGD), 5 treatment and 3 repetitions, with red dragon fruit peel pure addition 10%, 13%, 16%, 19% and 22% of main ingredients. Organoleptic testing showed, the different significant effect on color, taste, aroma, texture, overall acceptance, color quality and texture quality. Results of chemical analysis of antioxidant capacity were 14.33 – 18.23 mg/L and crude fiber content were 2.75 – 4.51% bw. Mud cake with red dragon fruit peel pure addition of 16% (P3) got the best results with color average with average 3.73 (liked), taste with average value 3.68 (liked), aroma with average value 3.58 (liked), overall acceptance with average value 4.11 (liked), color quality with average value 1.91 (pink) and texture quality with average value 2.28 (a bit dense). Results of chemical analysis of P3 showed antioxidant capacity 15.07 mg/L and a crude fiber content 3.04% bb so, the public can use it as reference for developing modifications and utilization of dragon fruit peel into nutritious preparations.